UJI AKTIVITAS JUS BUAH JAMBU BIJI BERDAGING MERAH (Psidium guajava L.) TERHADAP PENINGKATAN TROMBOSIT PADA MENCIT (Mus musculus L.) YANG DIINDUKSI KLORAMFENIKOL - Hosea, Cindy Trie Permatasari; Jamaluddin, Abdul Wahid; Adikurniawan, Yuko Mulyono (Fakultas Farmasi UMI, 2018)
Thrombocytopenia is the most common hemostatic disorder acquired in dogs and can be a life-threatening. Guava fruit and leaves extract are believed to improve thrombocyte counts. The purpose of this study was to prove that administration of guava juice could improveÂ thrombocyte count in mice that have thrombocytopenia after induced by chloramphenicol. We were used 24 mice as samples divided into 4 groups : KS group (given aquades for 12 days), KN group (induced by chloramphenicol for 7 days, then aquades on next 5 days), group P1 (induced by chloramphenicol for 7 days then guava juice 5 g/ml concentration on 5 next day); and group P2 (induced by chloramphenicol for 7 days then guava juice 10 g/ml concentration on the next 5 days). Thrombocyte count was measured three times, before treatment (day 0), after chloramphenicol induction (day 7), and after guava juice (day 12). Data of thrombocyte count was analyzed using one way Anova and Post Hoc LSD test. The results showed that the guava juice (Psidium guajava L.) concentration of 5 g/ml and 10 g/ml had significant effect (p <0,05) to increase platelet numbersÂ in mice after induced by chlorampenicol dose 30mg/30grBW.